High parity predicts use of long-acting reversible contraceptives in the extended postpartum period among women in rural Uganda - Ronald Anguzu; Hassard Sempeera; Juliet N. Sekandi (BMC, 2018)
Abstract Background The use of implants and Intra-uterine devices (IUD) during the post-partum period is very low in Uganda especially in rural settings. Long-acting reversible contraceptives (LARC) are known to be the most cost-effective for prevention of unintended pregnancy and unsafe abortions. This study aimed at determining the factors associated with long-acting reversible contraceptive use among women in the extended postpartum period in rural Uganda. Methods We conducted a household-based, cross-sectional study among 400 women in two rural communities in Mityana district, central Uganda. Eligible women were aged 15 to 45 years who had childbirth within 12 months of study enrollment in September 2014. The outcome variable was self-reported use of a LARC method, either IUD or implants in the extended postpartum period. The main independent variables were previous childbirths (parity), fertility desire, willingness to use modern contraception, duration of postpartum period and previous pregnancies (gravidity). A logistic regression model was run in STATA v12.0 to compute adjusted odds ratios (AOR) for factors that predicted LARC use statistically significant at p < 0.05. Results Four hundred respondents had a mean age of 27 years (SD = 12) and only 8.5% reported using a LARC method. Use of IUD and implant was 1.8% and 10.4% respectively. Most women using LARC (44.1%) had five or more childbirths (p = 0.01), 70.8% of non-LARC users were willing to use modern contraceptives (p = 0.07) and 2.5% ever had an induced abortion. Having five or more childbirths was independently associated with LARC use in the extended postpartum period (AOR = 4.07, 95%CI 1.08-15.4). Willingness to use modern contraception, desire for more children and postpartum duration had no significant association with LARC use in the extended postpartum period. Conclusion This study revealed low use of LARC within twelve months of child birth despite women's willingness to use them. High parity (≥5 childbirths) predicted LARC use. The next logical step is to identify barriers to using LARC in the extended postpartum period and design appropriate interventions to increase access and use especially in multi-parous women.